A Critical Race Theory Analysis of Institutional Racial Paralysis in Organizational Culture. (3rd September 2021) - Conyers, Addrain; Wright Fields, Christina
Abstract : This article uses critical race theory (CRT) to explore institutional racial paralysis (IRP) in organizational culture. Utilizing a CRT lens, the authors identify four stages of IRP: idleness, concealment, evolving modus operandi, and pervasive. The major tenets of CRT are utilized to reveal colorblindness and White hegemony as a justification for remaining idle on issues of race. The authors argue that IRP is not a new phenomenon, but rather a byproduct of institutional racism. This article joins an expanding list of scholarship encouraging discourse that engages CRT as an instrumental theory in contemporary issues of race in public administration.